Adaptation of Anti-HER2 Therapy During Adjuvancy in Localized Breast Cancer: A Case Report - Sumba-Chávez, Andrea D. (2025)
Localized HER2-positive breast cancer represents an aggressive subtype with a high risk of recurrence. Despite advances in adjuvant therapy, a significant proportion of patients do not achieve a complete pathological response after neoadjuvant treatment, which increases the risk of disease progression. Case Report: This report discusses the case of a 40-year-old premenopausal woman diagnosed with localized, multifocal HER2-positive breast cancer. The patient received neoadjuvant chemotherapy with anthracyclines, taxanes, and dual anti-HER2 blockade (trastuzumab and pertuzumab). After neoadjuvant therapy, residual disease was detected, leading to adjuvant treatment with T-DM1. Following eight cycles, the patient developed grade 2 pneumonitis, prompting the discontinuation of T-DM1 and the initiation of corticosteroid therapy. After recovery, adjuvant trastuzumab was administered. Given the high risk of recurrence, neratinib was introduced as extended adjuvant therapy. The patient tolerated neratinib well with prophylactic loperamide and completed one year of treatment. At the time of this report, she remains disease-free. Conclusion: This case underscores the importance of flexible adaptation of adjuvant HER2-targeted therapies in patients who encounter rare treatment-related complications. Although standardized protocols for managing such toxicities are not yet established, individualized treatment modifications, guided by clinical trial evidence, can optimize long-term outcomes.